Differences in Perceptions of Major Depressive Disorder Symptoms and Treatment Priorities Between Patients and Health Care Providers Across the Acute, Post-Acute, and Remission Phases of Depression - Baune, Bernhard T.; Christensen, Michael Cronquist (Frontiers in Psychiatry, 2019)
Limited data exist on concordance between patients’ and health care providers’ (HCPs) perceptions regarding symptoms of major depressive disorder (MDD) and treatment priorities, particularly across disease phases. This study examined concordance during the acute, post-acute, and remission phases of MDD. In an online survey, 2008 patients responded based on their experience with MDD, and 1046 HCPs responded based on their clinical experience treating patients with MDD. Questions included symptom frequency, treatment priorities, and impact on psychosocial functioning. Patients reported more frequent mood, physical, and cognitive symptoms than HCPs in the post-acute and remission phases, and greater impact on psychosocial functioning. Patients reported that all these symptoms require high treatment priority across the phases of MDD, generally to a greater extent than HCPs. Patients also gave high emphasis to addressing impairment in psychosocial functioning early in the treatment course. A substantial difference in the effectiveness of treating symptoms of MDD between patients and HCPs was observed. This is the first study to quantify, broadly, differences in perceptions of MDD symptom prevalence, severity, and treatment priorities across MDD phases, and highlights a need for improved communication between patients and HCPs about symptoms, impact on functioning, and treatment priorities across phases.